Pertanggungjawaban Hukum Influencer Judi Online Terhadap Masyarakat Yang Rugi Ditinjau Dari Hukum Perdata - Billy Sachio; Noor Saptanti (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
This study describes and examines the issue of the legal responsibility of online gambling promoters to people who lose due to influencers, considering the situation and conditions that are in need, of course, people will be tempted to obtain instant wealth. This study aims as an effort so that victims get proportionate attention in fulfilling their rights as victims to apply for restitution against online gambling influencers who advertise by providing false or untrue reviews. This research is a normative legal research that is perscriptive. Secondary data types include primary and secondary legal materials. The technique of collecting legal materials is carried out by literature study, then the analytical technique used is the deductive method. The results of this study show that victims can hold criminal and civil liability contained in Article 27 paragraph (2) jo. Article 45 paragraph (3) of Law number 1 of 2024 concerning online gambling, Law, Law 8 of 1999 concerning Consumer Protection, Article 1365 of the Civil Code concerning PMH, Article 1320 of the Civil Code concerning the legal terms of the agreement, and the Witness and Victim Protection Agency (LPSK).